Physicochemical Properties of Virgin Coconut Oil Extracted from Different Coconut (Cocos nucifera L) Varieties - Hewa Pathirana, Dilani; Yalegama, Chandi; Jayawardhana Arachige, Darshana; Senarathne, Malki (International Coconut Community Journal, 2021)
Virgin coconut oil (VCO) is a superior edible oil extracted from fresh coconut (Cocos nucifera L) kernel using mixed coconut varieties without considering the varietal effect. Therefore, this research focuses on the quality evaluation of VCO extracted from four types of coconut varieties, namely Sri lanka Tall×Tall (TT), a tall variety of Gon Thambili (GT), a tall variety of Ran Thambili (RT) and Philippines tall variety of San Ramon (SR). Mature coconuts from each variety were collected from the Bandirippuwa Estate of the Coconut Research Institute, Sri Lanka to extract VCO by cold press oil extraction method. The extractability of VCO from different varieties was investigated. Moisture, free fatty acid (FFA), fatty acid profile (gas chromatography), peroxide value (PV), color (Lovibond scale), total phenolic substances (Galic acid equivalent), antioxidant capacity (α,α-diphenyl-β-picrylhydrazyl, 0.1mM – DPPH method) and sun protection factor (SPF) of VCO extracted from each variety were analyzed. The experiment was conducted as a completely randomized design with three replicates. Data were analyzed using ANOVA using Tukey’s test by MINITAB 17. Oil extractability (58%-59%), FFA (0.04%-0.12%), color (0.43–0.93) and fatty acid profile of VCO did not show variation among varieties. A higher concentration of total phenolic substances was observed in GT (0.24±0.03mg GAE/100g) while antioxidant capacity (857.19±14.99mg/ml) and SPF (8.99±1.26) was rich in RT.